Deciphering Parkinson’s Disease through Eye Movements: A Promising Tool for Early Diagnosis in the Face of Cognitive Impairment - Xianglian Liao; Jian Yao; Hongyin Tang; Yilan Xing; Xin Zhao; Daao Nie; Ping Luan; Guihua Li (International Journal of Clinical Practice)
Cognitive dysfunction is the most common and important nonmotor symptom in Parkinson’s disease (PD) and can occur at any stage. However, there is still a lack of effective biomarkers to evaluate the decline in cognitive function and predict the progression of the disease, especially in the early stage. At present, the cognitive scale is widely used to evaluate the cognitive function of patients with PD, but its sensitivity and accuracy are relatively limited, especially in the early identification of mild cognitive impairment. Eye movement tracking is an advanced neurophysiological measurement method that serves as a powerful means to study the relationship between behavior and neural mechanisms. In recent years, eye movement tracking has been found to provide a nonverbal and less cognitive method to measure the disease progress of patients with cognitive impairment. Moreover, there is a good correlation between eye movement tracking and the traditional cognitive assessment scale, indicating that eye movement tracking can be used to evaluate and monitor the cognitive status, disease severity, and disease progression of patients with PD. Compared to the traditional cognitive scale, the eye movement detected by the instrument has better objectivity and repeatability. Existing studies have found that executive dysfunction is one of the most important manifestations of cognitive dysfunction in patients with PD and is related to an increase in the error rate of the saccade, an increase in the disinhibition of the delayed saccade task, and a prolongation of the saccade reaction time. This suggests that eye movement measurement plays an important role in the early diagnosis, progression, and differential diagnosis of PD and may even help to predict the disease progression of patients with PD and cognitive impairment. In this article, we review the correlation between cognitive impairment and eye movement disorder in patients with PD.